2019
DOI: 10.1111/ajpy.12225
|View full text |Cite
|
Sign up to set email alerts
|

Need for clinical neuropsychological assessment in headspace youth mental health services: A national survey of providers

Abstract: Objective: To determine the perceived met and unmet need for clinical neuropsychological assessment (CNA) in headspace youth mental health services Australia wide. Method: Brief online survey of headspace service providers exploring the number and types of clients seen, confidence in identifying neurocognitive impairments, and need, availability and usefulness of CNA. A total of 532 salaried, private, and in-kind service providers working across 103 primary headspace and headspace Youth Early Psychosis Program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
6
7
0
Order By: Relevance
“…Current study responders also identified a limited availability of neuropsychologists to conduct evaluations. This parallels findings from quantitative investigations of neuropsychology utilization (Allott et al, ; Fisher et al, ). Overall, many of these discrete clinician‐endorsed barriers appear interrelated.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Current study responders also identified a limited availability of neuropsychologists to conduct evaluations. This parallels findings from quantitative investigations of neuropsychology utilization (Allott et al, ; Fisher et al, ). Overall, many of these discrete clinician‐endorsed barriers appear interrelated.…”
Section: Discussionsupporting
confidence: 79%
“…There also appears to be a need to promote greater awareness of neuropsychology to clinicians, clients and their families within mental health settings as well as the broader community. This may help reduce potential stigma associated with neuropsychological assessments, with greater knowledge facilitating implementation in youth settings (Allott et al, ; Corrigan, ; Temple et al, ). Increasing site‐specific information regarding streamlined methods of accessing neuropsychology resources and when referrals are appropriate is encouraged.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations